Money Laundering: A Three-Step Secret Game - Md Arman (Advanced Qualitative Research, 2023)
This paper describes, theoretically, what money laundering is and how it is done following some partnered activities over time. This paper also looks for electronic money laundering and finds some related and predefined functions which are completed using electronic gadgets and the Internet. A systematic literature review is conducted by employing a meta-analysis approach. To give a clear view on money laundering, the author thinks it is necessary to make it clear first about the characteristics of money laundering, the reasons behind it, and how it negatively impacts the business and economy of a country. Money laundering is a crime in most nations, and economically developed countries built a strong fortress against money launderers, but laundering is not stopped. So, this paper tries to discover what and how the launderers launder and discover inventive ways to turn their unlawful cash lawful, which the legal authority cannot detect. This paper shows the step-by-step procedures of these globally illegal money-whitening activities, mostly theoretically.